Controlled superfusion of the rat spinal cord for studying non-synaptic transmission: an autoradiographic analysis - Beck, Heidemarie; Schröck, Helmut; Sandkühler, Jürgen (Journal of neuroscience methods, 1995)
Recently, evidence has been raised that long-term changes in the central nervous system are mediated by extrasynaptic spread of neuropeptides (‘volume…